Encyclopedia of social media and politics. Volume 1. - Harvey, Kerric (SAGE Reference, 2020)
Reader's Guide lists articles by the following topics: Celebrities and pioneers in social media and politics -- Congressional social media usage (most active members) -- Measuring social media's political impact -- Misuse of social media in the political arena: issues and ethics -- Social media, candidates, and campaigns -- Social media, politics, and culture -- Social media and networking web sites -- Social media and political unrest -- Social media and social issues, activism, and movements -- Social media concepts and theories -- Social media regulation, public policy, and actual practice -- Social media types, innovation, and technology